Enriching triboelectric signal characteristic toward vibration waveform recognition by electron-beam irradiation - Hu Bian; Fanzheng Zeng; Haoran Yu; Xingyi Song; Jia Liu; Xingke Zhao; Zhenming Chen; Chengmei Gui; Junjun Huang (Chemical Engineering Journal, 2026)

Fusicoccane glycosides from the endophytic fungus Talaromyces sp. DC-26 - Peng Zhou; Jingwen Yu; Xueying Deng; Jinyan Cai; Wenya Feng; Junjun Liu; Qin Li; Chong Dai; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

Large-strain self-weight consolidation model under double-drained conditions: A unified framework incorporating water weight effects - Cong Mou; Jiaxing Weng; Feng Ji; Jianhua Wang; Junjun Ni; Dechang Ren; Jin Yu (Transportation Geotechnics, 2026)

Engineered norfloxacin-derived carbonized polymer dots for synergistic antibacterial and anti-inflammatory periodontitis therapy - Xinyu Jiang; Yu Deng; Jia Liu; Huan Chen; Hongyan Lin; Yu Zhong; Junjun Liu; Xinchan Liu; Bai Yang (Chemical Engineering Journal, 2026)

Feasibility evaluation for cockroach from Periplaneta americana as a new protein feed ingredient in pigs - Zilin Li; Yu Cao; Meng Liu; Jingru Yuan; Jia Li; Wentao Huo; Mingyi Huang; Shuaishuai Kang; Shiyan Sui; Xiaokang Ma; Yujun Wu; Dandan Han; et al. (Animal Feed Science and Technology, 2026)

Urban Surface Deformation Monitoring Enhanced by E-SBAS: Multi-Source 3D Time-Series Integration - Xiaoyu Zhang; Shitai Wang; Min Yin; Zhengyang Xu; Zengyang Lu; Junjun Huang; Songchao Yu (Advances in Space Research, 2026)

Genome-wide identification of MATE gene family in potato and functional characterization of StMATE1/4/98 in response to aluminum stress - Junjun Huang; Guanzhuo Wang; Chang Yuan; Xin Chen; Juanjuan Yu; Huiling Gong; Huahua Wang (Plant Science, 2026)

Compensation for the initial capacity loss in lithium-ion batteries via controlled electrolyte decomposition at cathode - Jiajia Zhu; Tingyu Zhao; Qiuyu Jia; Hexiang Lan; Longfei An; Yuqi Jiang; Aiping Jin; Weiming Wang; Luying He; Jun Xiong; Junjun Peng; Ming Li; et al. (Chemical Engineering Journal, 2026)

A soybean EIN transcription factor confers resistance to Phytophthora sojae and favorable agronomic traits - Meng Liu; Jiaxin Yin; Xudong Wei; Junjun Song; Yaqun Dongye; Xi Chen; Xin Fang; Xinyue Yu; Yan Sun; Jihao Ju; Xiaoyu Chen; Junjiang Wu; et al. (Plant Cell Reports, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

Effects of foundation types on structural response to tunnelling in sand: A numerical investigation - Jingmin Xu; Zehui Yu; Yan Li; Junjun Ni (Computers and Geotechnics, 2026)

Integrating multi-stage interventions for harmful algal blooms effective management - Zhuwu Jiang; Jianxin Pan; Chengchun Shi; Xiao Yao; Huang Yu; Junjun Wang; Junjun Chen; Jyunhong Shen; Hai Yu; Wuqiang Zeng; Junlan Chen; Zhihao Lin; et al. (Journal of Environmental Management, 2026)

Elucidating the mechanism of sulfur reactions over NiFe2O4 oxygen carrier at atomic level - Cheng Shen; Yu Li; Daifen Chen; Xin Liu; Junjun Sun; Jintian He; Laihong Shen (Fuel, 2025)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

Investigating the variations in microbiome and volatilome characteristics of sauce-flavor Muqu across different grades and production rounds - Yu Mu; Linpei Liu; Junjun He; Hong Zhang; Shirui Yu; Zhiyu Zhu; Ying Huang; Mingyue Mou; Chunlin Zhang (Food Chemistry, 2025)

Involvement of nitric oxide-mediated cytosolic glucose-6-phosphate dehydrogenase in soybean resistance to heavy metal toxicity - Junjun Huang; Luyu Wang; Ziyu Jia; Kunxia Cheng; Rongzhi Han; Juanjuan Yu; Huahua Wang (Plant Cell Reports, 2025)

A multiple‐behaviors virtual fish model for simulating fish trajectory in vertical slot fishways - Xiaolong Chen; Xiaotao Shi; Xingyong Deng; Majid Rasta; Junjun Tan; Yu Wang; Yongqiang Jiang; Yanqin Bai (Journal of Fish Biology, 2025)
Fishways are essential for restoring river connectivity and facilitating fish migration, necessitating ongoing research for efficiency optimization. This study developed a fish behavior model to optimize fishway efficiency cost‐effectively. The model simulates swimming trajectories of Schizothorax wangchiachii within a vertical slot fishway incorporating upstream behavior, random behavior, obstacle avoidance, and swimming speed variations. The simulated trajectory exhibits a high consistency with 20 real trajectories, achieving a trajectory overlap rate of 86.7%. This result highlights the model's ability to accurately simulate fish movements, demonstrating its significant potential to revolutionize fishway design.

A review of the research progress in the enrichment of rare earth resources by biosorbents - Shiyu Shao; Junjun Wang; Hao Zhou; Xinyi Yu; Jue Kang; Min Huang; Zhu Chen; Hongbo Zhao; Guanzhou Qiu; Li Shen (Minerals Engineering, 2025)

Sustainable Fe(II) oxidation/reduction and release/recovery dual cycle in a multi-chamber Fe(III)/Peroxymonosulfate electrochemical system: Application, mechanism, and optimization - Minghao Yu; Meng Chen; Chenxu Yang; Jianrui Niu; Jing Zhang; Situ Mu; Ruina Zhang; Junjun Ma; Chun Liu (Chemical Engineering Journal, 2025)

Dual RNA sequencing reveals the interactions mechanism between Aspergillus fumigatus and Synechocystis sp. PCC6803 under Cd(II) exposure - Junjun Wang; Qinghua Tian; Jun Suo; Jue Kang; Hao Zhou; Xinyi Yu; Guanzhou Qiu; Li Shen (Journal of Environmental Chemical Engineering, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Prescribed performance rapid attitude maneuvering control based on time delay estimation for flexible spacecraft system with input deadzone - Junjun Liu; Yufu Cui; Haoping Wang; Xingyu Zhou; Linghui Yu (Advances in Space Research, 2025)

Pea power against microbes: Elucidating the characteristics and antimicrobial mechanisms of antimicrobial peptides obtained through enzymatic hydrolysis of pea protein isolate - Jiake Wang; Tongliang Yang; Wenwen Yu; Junjun Zhou; Yaqing Bian; Shuhong Li; Ye Chen (Food Bioscience, 2025)

Spherical Bi2MoO6 with oxygen vacancies via solvent manipulation for enhanced photocatalytic NO removal - Yu Wang; Junjun Wang; Qiuhui Zhu; Ke Zhao; Haitao Ren; Hong Kang; Meng Luo; Chuanyi Wang (Journal of Environmental Chemical Engineering, 2025)

An efficient fungi-biochar-based system for advancing sustainable management of combined pollution - Ying Xia; Minghui Deng; Tao Zhang; Junjun Yu; Xinda Lin (Environmental Pollution, 2025)

Redefining limits: Impact of nozzle diameter on film flow and atomization beyond the synchronizing radius - Yu Tan; Xudong Chen; Maojiang Jia; Bin Ding; Junjun Wu; Yuelin Qin (Chemical Engineering Journal, 2025)

Unlocking the potential of vinegar residue: A novel biorefining strategy for amino acid-enriched xylooligosaccharides and humic-like acid - Yuanyuan Zhu; Ruijun Tang; Yuting Cao; Yongjian Yu; Junjun Zhu (Waste Management, 2025)

Synergizing postharvest physiology and nanopackaging for edible mushroom preservation - Ming Gong; Tongyan Zhang; Yingying Wu; Junjun Shang; Erzheng Su; Yu Cao; Jianguo Zhang (Food Chemistry, 2025)

Cerebrospinal Fluid-Derived extracellular Vesicle-Inspired Multifunctional bone regeneration scaffold for cranial defect repair - Jie He; Yifan Zhang; Xiaolan Sun; Minjie Wang; Qing Zhang; Simin Liu; Shaojie Yu; Xuan Wang; Zhenxing Wang; Junjun Li; Xiaobin Jiang (Chemical Engineering Journal, 2025)

Mechanistic insight of fungal–microalgal pellets in photobioreactor for heavy-metal wastewater bioremediation - Junjun Wang; Qinghua Tian; Jue Kang; Hao Zhou; Xinyi Yu; Guanzhou Qiu; Li Shen (Bioresource Technology, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Periodically asymmetric responses of deep chlorophyll maximum to light and thermocline in a clear monomictic lake: Insights from monthly and diel scale observations - Jingyi Li; Qichao Zhou; Yue Dao; Di Song; Zhirong Yu; Junjun Chang; Erik Jeppesen (Science of The Total Environment, 2024)

Amylopectin from maize-derived carbonized polymer dots as a novel high-efficiency antioxidant for periodontitis treatment - Junjun Liu; Naibo Feng; Xinyu Jiang; Xirui Xin; Yubo Hou; Zhende Jiang; Laijin Lu; Weixian Yu; Bai Yang (Chemical Engineering Journal, 2024)

Silicon alleviates aluminum-induced programmed cell death through regulating the antioxidant defenses in soybean roots - Yuanyuan Yu; Ying Wang; Huanan Li; Yiwei Chen; Junjun Huang; Huahua Wang (Biologia, 2024)

Hybrid-tracked finite-time path following control of underactuated underwater vehicles with 6-DOF - Kaicheng Shen; Caoyang Yu; Ying Guo; Yiming Zhong; Junjun Cao; Xianbo Xiang; Lian Lian (Ocean Engineering, 2024)

Insights of using microbial material in fluoride removal from wastewater: A review - Linlin Cui; Junjun Wang; Hao Zhou; Shiyu Shao; Jue Kang; Xinyi Yu; Hongbo Zhao; Li Shen (Journal of Environmental Management, 2024)

A review of cleaner production of glass-ceramics prepared from MSWI fly ash - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Junjun Wu; Bin Ding (Journal of Environmental Management, 2024)

Structural disorder Triggered by small organic molecules Boosting δ-MnO2 cathode for Ultra‐Stable aqueous zinc ion batteries - Junjun Tang; Shuan Ma; Yu Jiang; Lufeng Yang; Jie Chen; Xuemin Yan; Bohong Chen; Zhenxiong Huang (Chemical Engineering Journal, 2024)

Co-porphyrin-based metal-organic framework for light-driven efficient green conversion of CO2 and epoxides - Jinxia Liang; Xin Jiang; Xinrui Zhang; Hao Yu; Junjun Shi; Ming Wang (Chemical Engineering Journal, 2024)

Dissecting the mechanism of synergistic interactions between Aspergillus fumigatus and the microalgae Synechocystis sp. PCC6803 under Cd(II) exposure: insights from untargeted metabolomics - Li Shen; Jue Kang; Junjun Wang; Shiyu Shao; Hao Zhou; Xinyi Yu; Min Huang; Weimin Zeng (Journal of Hazardous Materials, 2024)

N-doped carbon achieved by pyrolyzing urea and active carbon for the capacitive deionization coupled PMS oxidation system - Meng Chen; Chenxu Yang; Minghao Yu; Mengyao Han; Zihan Meng; Tian Zhao; Jianrui Niu; Situ Mu; Jing Zhang; Junjun Ma; Chun Liu (Desalination, 2024)

Depth control analysis of Smartfloat using sea trail data and parameter identification - Ping Cheng; Junjun Cao; Jialuan Xiao; Yiming Zhong; Caoyang Yu (Ocean Engineering, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Combining metabolomics and transcriptomics to analyze key response metabolites and molecular mechanisms of Aspergillus fumigatus under cadmium stress - Qinghua Tian; Junjun Wang; Shiyu Shao; Hao Zhou; Jue Kang; Xinyi Yu; Min Huang; Guanzhou Qiu; Li Shen (Environmental Pollution, 2024)

Experimental and theoretical study on performance of Cu-Fe spinel supported with certain inerts during chemical looping combustion - Yu Li; Li Wang; Daifen Chen; Jing Liu; Wei Fan; Junjun Sun (Chemical Engineering Journal, 2024)

Optimization and mechanism studies for the biosorption of rare earth ions by Yarrowia lipolytica - Li Shen; Xinyi Yu; Hao Zhou; Junjun Wang; Hongbo Zhao; Guanzhou Qiu; Zhu Chen (Environmental Science and Pollution Research, 2024)

Dynamic analysis and simulations of a deep-sea floating mining vehicle multi-body system under real-world operating conditions - Jialuan Xiao; Ping Cheng; Junjun Cao; Rui Lin; Mengzhi Luo; Caoyang Yu; Baoheng Yao; Yongli Hu (Ocean Engineering, 2024)

SNX14 inhibits autophagy via the PI3K/AKT/mTOR signaling cascade in breast cancer cells - Sha Lv; Hongyan Jiang; Lingyan Yu; Yafei Zhang; Liangliang Sun; Junjun Xu (Journal of Molecular Histology, 2024)

Clusterin is a Potential Therapeutic Target in Alzheimer’s Disease - Nazhakaiti Palihati; Yuanhong Tang; Yajuan Yin; Ding Yu; Gang Liu; Zhenzhen Quan; Junjun Ni; Yan Yan; Hong Qing (Molecular Neurobiology, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

Metabolomics-based analysis of the interaction effects and stress response mechanisms in the co-culture system of fungi and microalgae under cadmium stress - Junjun Wang; Qinghua Tian; Jue Kang; Hao Zhou; Xinyi Yu; Guanzhou Qiu; Li Shen (Journal of Cleaner Production, 2024)

Carbon felt (CF) acted as an “ionic capacitor” to enhance flow electrode capacitive deionization (FCDI) desalination performance - Yunke Li; Junjun Ma; Minghao Yu; Jianrui Niu; Jiarong Gu; Meng Chen; Puming Zhang; Jing Zhang; Chun Liu (Desalination, 2024)

Physiological regulation of microalgae under cadmium stress and response mechanisms of time-series analysis using metabolomics - Junjun Wang; Qinghua Tian; Hao Zhou; Jue Kang; Xinyi Yu; Guanzhou Qiu; Li Shen (Science of The Total Environment, 2024)

Comparison of biosorption behavior and mechanism of La3+, Sm3+, Y3+, Nd3+, Er3+ by Aspergillus niger and Bacillus sp - Hao Zhou; Junjun Wang; Shiyu Shao; Xinyi Yu; Jue Kang; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Journal of Water Process Engineering, 2024)

Nitrogen-rich penicillin residue biochar for activation of peroxymonosulfate for an efficient degradation of tetracycline and its dual-pathway mechanism - Jianrui Niu; Hua Jia; Minghao Yu; Jinyu Zhu; Junjun Ma; Zhuang He; Weizhang Zhong; Yongjiang Hou; Yankai Guo (Process Safety and Environmental Protection, 2024)

Performance enhancement of ice storage capsules by biomimetic fins - Liangyu Wu; Jie Yu; Junjun Yang; Wei Gao; Chengbin Zhang; Cheng Yu (International Journal of Refrigeration, 2024)

Study of aromatic extraction from light cycle oil from the viewpoint of industrial applications - Junjun Shi; Xiaojia Wu; Guojia Yu; Lei Xi; Hu Zou; Wei Wu; Zhiyong Zhou; Zhongqi Ren (Fuel, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Preparation of dual-functional packaging films containing green tea essential oil microcapsules for strawberry preservation: Excellent barrier properties and antioxidant activity - Weijie Zhao; Lianjun Yu; Yali Gu; Weijia Ma; Kehui Wang; Junjun Liang; Qi Liu (Food Bioscience, 2023)

Enhancing sustainable valorization: Harmless synergistic melting treatment for high-value vitreous products from MSWI fly ash and electrolytic manganese residue - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Bin Ding; Junjun Wu (Waste Management, 2023)

Stabilizing Cr(Ⅲ) deriving from tannery sludge with kaolin and organic matter - Junjun Ma; Tao E; Shuyi Yang; Liang Chen; Ying Cheng; Jia Yu; Yun Li (Environmental Research, 2023)

Utilization of Aspergillus niger strain to leach rare earth elements based on untargeted metabolomics analysis - Hao Zhou; Xinyi Yu; Junjun Wang; Guanzhou Qiu; Hongbo Zhao; Li Shen (Chemical Engineering Journal, 2023)

Uncovering the origin of surface-redox pseudocapacitance of molybdenum phosphides enables high-performance flexible sodium-ion capacitors - Yalong Jiang; Runya Han; Jun Dong; Ruohan Yu; Shuangshuang Tan; Fangyu Xiong; Qiulong Wei; Junjun Wang; Lianmeng Cui; Haiyang Tian; Yingkui Yang; Qinyou An (Chemical Engineering Journal, 2023)

Key metabolites and regulatory network mechanisms in co-culture of fungi and microalgae based on metabolomics analysis - Junjun Wang; Qinghua Tian; Hao Zhou; Jue Kang; Xinyi Yu; Li Shen (Bioresource Technology, 2023)

Energy optimal depth control for multimodal underwater vehicles with a high accuracy buoyancy actuated system - Junjun Cao; Rui Lin; Chunhu Liu; Hao Feng; Caoyang Yu; Baoheng Yao; Lian Lian (Ocean Engineering, 2023)

Dynamic modeling and switching analysis of all-attitude multimode underwater vehicle for multidimensional data acquisition - Rui Lin; Junjun Cao; Jialuan Xiao; Caoyang Yu; Chunhu Liu; Baoheng Yao; Lian Lian (Ocean Engineering, 2023)

Solution-catalyzed carbothermal reduction of argo-waste SiO2 enables low-temperature and fast synthesis of Si(Ⅱ)-C anode - Zi'ang Liu; Ruohan Yu; Shaohua Zhu; Jiashen Meng; Xuanpeng Wang; Chaojiang Niu; Lianmeng Cui; Fan Qiao; Junjun Wang; Liqiang Mai (Chemical Engineering Journal, 2023)

Highly sensitive, wide-pressure and low-frequency characterized pressure sensor based on piezoresistive-piezoelectric coupling effects in porous wood - Jingjing Luo; Feihua Liu; Ao Yin; Xue Qi; Jiang Liu; Zhongqi Ren; Shiqiang Zhou; Yuxin Wang; Yang Ye; Qingzhi Ma; Junjun Zhu; Kang Li; et al. (Carbohydrate Polymers, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

A multifunctionally reversible detector: Photoacoustic and dual-channel fluorescence sensing for SO2/H2O2 - Yicai Zhu; Junjun Wang; Yingyong Ni; Qingpeng Rao; Xiaojiao Zhu; Jianhua Yu; Sen Wang; Hongping Zhou (Analytica Chimica Acta, 2023)

Synthesis of a micro-nano FeOx/MnOx modified large volume non-enamel ceramsites for selective and efficient adsorption of cadmium - Junkang Guo; Xianwei Yu; Muhammad Haris; Tian Liu; Jiayuan Wang; Junjun Zhao; Yifan Li; Chao Zhang (Journal of Environmental Chemical Engineering, 2023)

Mitochondria-associated endoplasmic reticulum membranes participate mitochondrial dysfunction and endoplasmic reticulum stress caused by copper in duck kidney - Junjun Peng; Xueyan Dai; Huiqin Fan; Chenghong Xing; Yu Zhuang; Xiaona Gao; Huabin Cao; Guoliang Hu; Fan Yang (Environmental Science and Pollution Research, 2023)

Advanced Marine Craft Model Identification via Multi-Kernel Weighted Least Square Support Vector Machine and Characteristic Model Techniques - Tianqi Pei; Caoyang Yu; Yiming Zhong; Junjun Cao; Lian Lian (Journal of Marine Science and Engineering, 2023)
This paper combines the piecewise Cubic Hermite (CH) interpolation algorithm and the weighted least square support vector machine (WLS-SVM) to improve identification accuracy for marine crafts built based on the characteristic model. The characteristic model is first used to describe the heading dynamics of marine crafts and is a superior model to the traditional response model in both accuracy and complexity. Especially in order to improve identification accuracy, a CH-based data preprocessing strategy is utilized to densify and smooth data for further accurate identification. Subsequently, the combination of the linear kernel function and the Gaussian kernel function is introduced in the conventional WLS-SVM method, which renders global and local performance improvements compared with the conventional WLS-SVM method. Finally, informative maneuvers composed of Zigzag and Sine are carried out to test the performance of the improved identification method. Compared to the conventional LS-SVM method based on the response model, the root mean square error of the proposed CH-MK-WLS-SVM method based on the characteristic model is reduced by an order of magnitude in the presence of sensor noise.

Improving cold-adaptability of mesophilic cellulase complex with a novel mushroom cellobiohydrolase for efficient low-temperature ensiling - Ming Gong; Ying Wang; Dapeng Bao; Shan Jiang; Hongyu Chen; Junjun Shang; Xiaojun Wang; Hnin Hnin Yu; Gen Zou (Bioresource Technology, 2023)

Prediction for odor gas generation from domestic waste based on machine learning - Yuanyan Jiang; Jiawei Huang; Wei Luo; Kejin Chen; Wenrou Yu; Wenjun Zhang; Chuan Huang; Junjun Yang; Yingzhou Huang (Waste Management, 2023)

Identification of PP2C Genes in Tibetan Hulless Barley (Hordeum vulgare var. nudum) Under Dehydration Stress and Initiatory Expression and Functional Analysis of HvPP2C59 - Junjun Liang; Ling Yi; Lilan Li; Haili Zhang; Yunshu Zhang; Guangbing Deng; Hai Long; Maoqun Yu (Plant Molecular Biology Reporter, 2022)

Relationship between meteorological factors and mortality from respiratory diseases in a subtropical humid region along the Yangtze River in China - Lingxiang Yu; Junjun Zhu; Ming Shao; Jinian Wang; Yubo Ma; Kai Hou; Huijun Li; Jiansheng Zhu; Xiaoyun Fan; Faming Pan (Environmental Science and Pollution Research, 2022)

Genetic dissection of quantitative trait loci for grain size and weight by high-resolution genetic mapping in bread wheat (Triticum aestivum L.) - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Juanyu Zhang; Xvebing Qiu; Xi Pu; Wuyun Yang; Jun Li; Zehou Liu; et al. (Theoretical and Applied Genetics, 2022)

Identification of HvLRX, a new dehydration and light responsive gene in Tibetan hulless barley (Hordeum vulgare var. nudum) - Junjun Liang; Haili Zhang; Ling Yi; Yawei Tang; Hai Long; Maoqun Yu; Guangbing Deng (Genes & Genomics, 2021)

Identification and validation of two major QTLs for spike compactness and length in bread wheat (Triticum aestivum L.) showing pleiotropic effects on yield-related traits - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Xvebing Qiu; Xi Pu; Jun Li; Zehou Liu; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

Astragaloside protects rat brain from microwave-induced functional injuries via restoring acetylcholine and normalizing electroencephalogram - Li Zhao; Yunbo Sun; Chao Yu; Junjun Chen; Xinping Xu; Xueyan Zhang; Hui Wang; Jing Zhang; Haoyu Wang; Ji Dong; Binwei Yao; Hongmei Zhou; et al. (Environmental Science and Pollution Research, 2020)

Metabolic characteristics and nutrient utilization in high-feed-efficiency pigs selected using different feed conversion ratio models - Beibei He; Tiantian Li; Wei Wang; Hang Gao; Yu Bai; Shuai Zhang; Jianjun Zang; Defa Li; Junjun Wang (Science China Life Sciences, 2019)

Transcriptome and metabolome analysis of Pichia stipitis to three representative lignocellulosic inhibitors - Yuanyuan Zhu; Lu Wu; Junjun Zhu; Yong Xu; Shiyuan Yu (Archives of Microbiology, 2019)

Characterization of extracellular polysaccharide/protein contents during the adsorption of Cd(II) by Synechocystis sp. PCC6803 - Li Shen; Zhanfei Li; Junjun Wang; Ajuan Liu; Zhenhua Li; Runlan Yu; Xueling Wu; Yuandong Liu; Jiaokun Li; Weimin Zeng (Environmental Science and Pollution Research, 2018)

Land scale biogeography of arsenic biotransformation genes in estuarine wetland - Si‐Yu Zhang; Jian‐Qiang Su; Guo‐Xin Sun; Yunfeng Yang; Yi Zhao; Junjun Ding; Yong‐Shan Chen; Yu Shen; Guibing Zhu; Christopher Rensing; Yong‐Guan Zhu (Environmental Microbiology, 2017)
Summary As an analogue of phosphorus, arsenic (As) has a biogeochemical cycle coupled closely with other key elements on the Earth, such as iron, sulfate and phosphate. It has been documented that microbial genes associated with As biotransformation are widely present in As‐rich environments. Nonetheless, their presence in natural environment with low As levels remains unclear. To address this issue, we investigated the abundance levels and diversities of aioA , arrA , arsC and arsM genes in estuarine sediments at low As levels across Southeastern China to uncover biogeographic patterns at a large spatial scale. Unexpectedly, genes involved in As biotransformation were characterized by high abundance and diversity. The functional microbial communities showed a significant decrease in similarity along the geographic distance, with higher turnover rates than taxonomic microbial communities based on the similarities of 16S rRNA genes. Further investigation with niche‐based models showed that deterministic processes played primary roles in shaping both functional and taxonomic microbial communities. Temperature, pH, total nitrogen concentration, carbon/nitrogen ratio and ferric iron concentration rather than As content in these sediments were significantly linked to functional microbial communities, while sediment temperature and pH were linked to taxonomic microbial communities. We proposed several possible mechanisms to explain these results.

Oxidative Modification and Its Implications for the Neurodegeneration of Parkinson’s Disease - Junjun Zhao; Shuqing Yu; Yan Zheng; Hui Yang; Jianliang Zhang (Molecular Neurobiology, 2017)

Effects of endogenous salicylic acid synthesized through PAL and ICS pathway on baicalin and baicalein accumulation in Scutellaria baicalensis Georgi - Hu Su; Chao Yu; Junjun Shang; Xin Yan; Pengfei Liao; Youlin Zhu; Yanchun Gong; Bin Zeng (Acta Physiologiae Plantarum, 2016)

The role of the PM2.5-associated metals in pathogenesis of child Mycoplasma Pneumoniae infections: a systematic review - Wei Hou; Xijin Xu; Yongge Lei; Junjun Cao; Yu Zhang; Liang Chen; Xia Huo (Environmental Science and Pollution Research, 2016)

Comparative analysis of genetic structure in Magnaporthe oryzae isolates from indica and japonica hosts in China - Junjun Shang; Yina Wang; Liu Su; Mansi Luo; Xin Yan; Chao Yu; Youlin Zhu (Journal of General Plant Pathology, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

A Single Nucleotide Polymorphism of Nud Converts the Caryopsis Type of Barley (Hordeum Vulgare L.) - Shuiyang Yu; Hai Long; Guangbing Deng; Zhifen Pan; Junjun Liang; Xingquan Zeng; Yawei Tang; Nyima Tashi; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Localization of the powdery mildew resistance gene Pm07J126 in wheat (Triticum aestivum L.) - Shuiyang Yu; Hai Long; Guangbing Deng; Zhifen Pan; Junjun Liang; Maoqun Yu (Euphytica, 2015)

Erratum to: Characterization of a genome-specific Gypsy-like retrotransposon sequence and development of a molecular marker specific for Dasypyrum villosum (L.) - Jie Zhang; Hai Long; Zhifen Pan; Junjun Liang; Shuiyang Yu; Guangbing Deng; Maoqun Yu (Journal of Genetics, 2013)

Characterization of a genome-specific Gypsy-like retrotransposon sequence and development of a molecular marker specific for Dasypyrum villosum (L.) - JIE ZHANG; HAI LONG; ZHIFEN PAN; JUNJUN LIANG; SHUIYANG YU; GUANGBING DENG; MAOQUN YU (Journal of Genetics, 2013)

Assessing land ecological security in Shanghai (China) based on catastrophe theory - Shiliang Su; Dan Li; Xiang Yu; Zhonghao Zhang; Qi Zhang; Rui Xiao; Junjun Zhi; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2011)